Culturable Yeast Diversity Associated with Industrial Cultures of the Microalga Microchloropsis gaditana and Their Ability to Produce Lipids and Biosurfactants - Madalena Matos; Mónica A. Fernandes; Inês Costa; Natacha Coelho; Tamára F. Santos; Veronica Rossetto; João Varela; Isabel Sá-Correia (Journal of Fungi)
The marine oleaginous microalga Microchloropsis gaditana (formerly Nannochloropsis gaditana) exhibits a high capacity to thrive in a broad range of environmental conditions, being predominantly utilized as feed in aquaculture. This article reports the characterization of the culturable yeast population present during the scale-up process of M. gaditana cultivation at Necton S.A. facilities, from 5 L flasks until tubular photobioreactors. The 146 yeast isolates obtained, molecularly identified based on D1/D2 and ITS nucleotide sequences, belong to the species Rhodotorula diobovata, R. mucilaginosa, R. taiwanensis, R. sphaerocarpa, Vishniacozyma carnescens, Moesziomyces aphidis, and Meyerozyma guilliermondii. The yeast abundance was found to increase throughout upscaling stages. The yeast populations isolated from microalgal cultures and water samples share phylogenetically close isolates, indicating a possible common source. The impressive high percentage of red yeasts isolated (90%) is consistent with the recognized role of carotenoid pigments in yeast photoprotection. Sixty yeast isolates were tested for lipid (Nile Red staining) and biosurfactant (oil drop dispersion and emulsification index) production. Results revealed that these capacities are common features. Microbial lipids and biosurfactants have promising biotechnological applications. Moreover, biosurfactants can fulfill various physiological roles and provide advantages in natural environments contributing to the promising use of yeasts as probiotics in microalgae production.